ANÁLISE TÉCNICA DE SISTEMAS DE PRODUÇÃO NO MUNICÍPIO DE GIRUÁ - Schwertner, Diogo V.; Gaviraghi, Fernando; Martins, João A. K.; Rosso, Lidiane V.; Carbonera, Roberto; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo